Akuisisi Data Pressure Transmitter melalui CX Supervisor pada STEM Pressure Measurement and Control Plant - Muhammad Syafei Gozali; Aditya Gautama Darmoyono; Heru Wijanarko; Asrizal Deri Futra; Kamarudin Kamarudin; Clara Anastasya Br Lumban Tobing (Journal of Applied Electrical Engineering, 2023)
Process control is one of the automation techniques that has been commonly used to control pressure, temperature, flow and fluid level in industrial factories, which aims to maximize production, maintain product quality levels, safety in production, and create a more economical production process. Based on these needs and situation Politeknik Negeri Batam begin to developing laboratorial module for the students. One of these modules is STEM Pressure Measurement and Control Plant with developed by adding a data acquisition system based on PLC CP1H and CX Supervisor application as data presentation element. The results of this study indicate that the application of the CX Supervisor and PLC CP1H has supported the development of learning, especially in the practice of process measurement and control. From the test results it can be seen that the three pressure transmitters used have linear characteristics according to the specifications of the device. From the test results of the proposed data acquisition system, the measurement results show a value that is close to the actual value with a deviation value of -0.1"“0.17 and standard deviations of 0.088, 0.075, and 0.107 and standard errors of 0.024, 0.021, and 0.030, respectively for pressure transmitter with capacitance, piezoresistive, and extensimeter types